(untitled) (Journal of Asian Development Studies, 2013)
In this study influential factors on life insurance demands in Iran were studied. Firstly, by using previous study results and interviewing with experts different factors were identified and classified under main groups. The required information and Data were gathered by two questionnaires. First questionaire was filled by managers and sellers in Iran insurance agencies in Semnan Province and data were analyzed by statistical test. Then in order to prioritize the factors another questionnaire (pairwise comparison questionnaires) was provided and filled by experts and after drawing the decision tree factors were prioritized by AHP method. These results illustrate that life insurance identity, structural, administrative, personal and cultural factors are respectively the most influential factors on life insurance demand in Semnan province agencies of Iran insurance. At last, in addition to prioritizing all the main factor categories, suggestions in order to increase demand and to develope insurance in Iran were presented.